To Sir with Love: the relations between teacher qualification and student performance in Accounting - Miranda, Gilberto José; Nova, Silvia Pereira de Castro Casa; Cornacchione Jr, Edgard Bruno (Review of Business Management, 2013)
Accounting scholars who discuss the teaching of Accounting highlight two fundamental types of qualification for teaching staff in Accountancy programs: academic qualification (AQ), which refers to the teacher’s preparation for research; and professional qualification (PQ), defined by the teacher’s connection with current professional practices in the job market. Educational literature on higher education teaching, in turn, appoints a third type: pedagogical qualification (PeQ), which relates to the systemized preparation for teaching practice in the university context. Considering undergraduate Accountancy students’ low performance levels in the National Exam for the Assessment of Student Performance (Exame Nacional do Desempenho dos Estudantes/Enade), this research aimed to investigate the relations between student performance and teacher qualification. To identify variables related to teaching staff qualification, a questionnaire was developed, validated and applied in 218 higher education institutions (HEIs) that offer undergraduate Accountancy programs. These variables were compared with graduates’ performance at the same institutions, verified on ENADE’s basis, using linear regression and correlation analysis. The results partially confirm the established hypotheses: only academic qualification shows a significant regression coefficient at 5% (p-value = 0.000) and a significant positive correlation at 1%. Professional and pedagogical qualification showed no significant correlations. The AQ rate at public HEIs is also significantly higher than at private HEIs.